Posteromedial rotatory instability of the elbow: What the radiologist needs to know. Issue 141 (August 2021) - Al-Ani, Zeid; Wright, Andrew; Ricks, Matthew; Watts, Adam C.
Highlights: Elbow posteromedial rotatory instability consists of an anteromedial coronoid fracture with proximal avulsion of the lateral collateral ligaments and ulnar collateral ligament posterior bundle tear. It can lead to persistent elbow instability, progressive cartilage damage and early osteoarthritis. Surgical treatment is indicated in patients with ongoing instability. CT and MRI can provide valuable information about the coronoid fracture morphology and the degree of ligamentous injuries respectively, and help guide the management decisions. Abstract: Varus posteromedial rotatory instability of the elbow joint is a relatively new subject described for the first time in 2003. It occurs secondary to axial loading of the elbow with varus force and internal rotation of the forearm. There is usually a specific pattern of osseous and soft tissue injuries that can be recognized on imaging. This includes an anteromedial coronoid fracture and avulsion of the lateral collateral ligament complex from its humeral attachment. Ulnar collateral ligament complex injury is also reported, particularly its posterior bundle which plays an important role in posteromedial elbow joint stability. There is high incidence of early osteoarthritis secondary to the resultant varus instability and increased contact pressure at the ulnohumeral joint. Surgical fixation of the coronoid fracture and ligamentous reconstruction maybe indicated to prevent this recurrent instability. The article reviews the key radiological features of posteromedial rotatory instability with multiple examples from different imaging modalities. The relevant anatomy of the elbow joint stabilising structures will be illustrated, in particular the coronoid process anatomy and the O'Driscoll classification for coronoid process fractures. Radiologists should be familiar with the imaging findings of posteromedial rotatory instability.